Trade in French books in Zagreb: 1796-1823 (Libellarium: journal for research in the field of information and related sciences, 2012)
The intention of this paper is to contribute to the picture of the book trade in Zagreb in the late 18th and early19th century. The objectives of the research were to find out which booksellers’ catalogues were available in Croatian capital Zagreb in that period and to illustrate the conclusions that can be drawn from the information gathered by focusing on a narrow topic: trade in French books in a particular period. A focus on French books was inspired by the importance of French culture in Europe of that time. The research included eight available catalogues published by three prominent Zagreb-based booksellers between 1796 and 1823. The resources were observed and their contents, format and internal organisation described which was followed by comparative analysis of 245 French titles indexed in these catalogues. Conclusions have been suggested about the availability of French books in Zagreb as well as pricing policy and other practices of the booksellers of that time. Possible contribution to book history in Croatia is not only in the results but also in the type of analysis performed.
Keywords: booksellers’ catalogues; book trade; French books; printers; Antun Novosel; Franjo Rudolf; Franjo Župan; history of books; Zagreb